Conception of Sanctions for Same-Sex Marriage Couples in the Perspective of Balinese Customary Law (Comparison of Laws in the United States) - I Made Wata Jiwana; Putu Eka Trisna Dewi (Jurnal Hukum Prasada, 2022)
In Balinese customary law, same-sex sexual intercourse is known as â€œsalah kramaâ€, or sexual intercourse with wrong partners and it is strictly prohibited in Hindu law. The reason is the situation will make the offenders become cuntaka, leteh or impure. The purpose of this study is to analyse and reveal the paradigm of same-sex marriage from the perspective of international law and customary sanctions against same-sex marriage couples in Bali. The type of research used in this study is normative legal research. Based on analysis, the results of this study revealed that the United States governmentâ€™s policy paradigm regarding same-sex marriage can be seen from the United States Supreme Court Decision which issued a policy that completely changed the existence of the LGBT community in the United States. Furthermore, the concept of customary sanctions against same-sex marriage couples in Bali is made in the form of giving customary sanctions to those practicing LGBT that must be executed strictly. The customary sanctions that can be given take the form of arta danda, sangaskara danda, and jiwa danda.